If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5y + 4) + -1(3 + 4y) = 5 Reorder the terms: (4 + 5y) + -1(3 + 4y) = 5 Remove parenthesis around (4 + 5y) 4 + 5y + -1(3 + 4y) = 5 4 + 5y + (3 * -1 + 4y * -1) = 5 4 + 5y + (-3 + -4y) = 5 Reorder the terms: 4 + -3 + 5y + -4y = 5 Combine like terms: 4 + -3 = 1 1 + 5y + -4y = 5 Combine like terms: 5y + -4y = 1y 1 + 1y = 5 Solving 1 + 1y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 1y = 5 + -1 Combine like terms: 1 + -1 = 0 0 + 1y = 5 + -1 1y = 5 + -1 Combine like terms: 5 + -1 = 4 1y = 4 Divide each side by '1'. y = 4 Simplifying y = 4
| 6+n+9=20 | | P/3=81 | | 3x*(4x+1)= | | 8v-16=150 | | (7a^2+7a-2)+(8a^2-2a-3)= | | 1/3(x-1)=5x-4(x-1)+7/3 | | 6(3x-1)/8=6 | | 1.5x+0.6=14 | | 12d-9=18d+9 | | 21x^2-60x-96=0 | | 8t+4q=12 | | 7/4w-3/7w=1/14 | | 18x-6=42 | | 24x-10=21x-4 | | c/2=1 | | -3(4r-8)=-6 | | 450=(15)(25)+b | | 1/5=z+3/5 | | log[4](x^2-x+2)=2 | | 6u-8=22 | | 1.5y+6x=13 | | 450=15+b | | 3t+2=32 | | 3x^2+y^2-6x=0 | | 10x-3=3x+18 | | A-9*5/2-4+12/3+7=A | | 3k+16=112 | | -5(10-3x)=25 | | 96=x+3x+6 | | 150=2lw+2lh+2wh | | 1/2x+4x-1/2x+60 | | 25000=8N+5000 |